Thieves and Bandits and their Impact on Disrupting Economic Activities in the Islamic Mashreq Cities - Abaid, Taha Kh.; Ahmed, Adris M.H. (Humanities Journal of University of Zakho, 2017)
Acts of thieves and acts of banditry are considered the dirtiest acts deprived by God. As mentioned in the Holly Quran “as for the man or woman who is guilty of theft, recompense them by cutting off their hands for their crimes. that is the punishment from Allah. Allah is mighty, wise.(38)”. These acts affected the economy and trade of thecities as well as stealing the commercial caravans and pilgrimscaravans which affected Muslims’ interests in such areas. Because of such acts, importing and exporting of goods became more difficult to and from such areas. Moreover, taxes gained from trade were also affected by such acts. Since these theft acts affected the tradeand economy of Islamic states in a bad way, Islamic states should havebeen ready to fight these thieves to secure commercial routes. The acts of thieves were more active during the weakness of the Abbasid state. Thieves usually make use of political circumstances to conduct their criminal acts. On the contrary, when the statesare strong,they can not conduct their criminal acts.